2008
DOI: 10.1159/000150446
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Regulation of cAMP/Protein Kinase A Pathway in Corneal Epithelium and Endothelium

Abstract: Purpose: The G-protein-coupled receptor/cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA) pathway is one of the most common and versatile signal pathways in eukaryotic cells. The aim of this study was to characterize subtypes of adrenergic G-protein-coupled receptors and their influence on cAMP concentration and PKA activity in bovine corneal epithelial and endothelial cells. Procedures: Adrenergic receptors and PKA were studied using polyclonal antibodies. cAMP concentration was determined with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 47 publications
0
26
0
2
Order By: Relevance
“…These inhibitors have similar structures; however, Guanabenz is also a potent agonist of the α2-adrenergic receptor (Das et al, 2015; Tsaytler et al, 2011). Because this receptor has been reported in corneal epithelial cells (Grueb et al, 2008), we studied both compounds to exclude any contribution of adrenergic signaling. GADD34/PP1 inhibitors showed dose-dependent inhibition of the hyperosmolarity-induced SNAT2 transport activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These inhibitors have similar structures; however, Guanabenz is also a potent agonist of the α2-adrenergic receptor (Das et al, 2015; Tsaytler et al, 2011). Because this receptor has been reported in corneal epithelial cells (Grueb et al, 2008), we studied both compounds to exclude any contribution of adrenergic signaling. GADD34/PP1 inhibitors showed dose-dependent inhibition of the hyperosmolarity-induced SNAT2 transport activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Stimulation and inhibition of the corneal cAMP/PKA pathway may play a role in important corneal functions such as wound healing and homeostasis. 3 Accordingly, cAMP potentiates the stimulation of corneal epithelial migration by epidermal growth factor in vitro, suggesting that endogenous cAMP might function as a modulator of epithelial wound healing promoted by this growth factor in vivo. 4 It has also been demonstrated that topical application of agents known to increase cAMP increase tear secretion.…”
Section: Early Publication On Intraoperative Retinoscopymentioning
confidence: 98%
“…They also reported the deficiencies of the latter method compared with intraoperative retinoscopy. The authors apparently overlooked my original publication 3 Early flap dislocation with perioperative brimonidine use in laser in situ keratomileusis…”
Section: Early Publication On Intraoperative Retinoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, brimonidine inhibits protein kinase A [Grueb et al, 2008]. Interestingly, Navaratnam et al [1996] demonstrated that the proliferation and regeneration of the avian auditory epithelium depends on the activation of protein kinase A, which is cAMP-dependent, and that inhibition of protein kinase A correlates with decreased regeneration.…”
mentioning
confidence: 99%